Contrast affects stimulus detection in natural scenes - Lopes, Gabriel; Tavares, Mara; Mendonça, Catarina (Frontiers in Human Neuroscience, 2025)
How can we predict if a brief stimulus will be detected or perceived when embedded in a dynamic natural scene, such as those we encounter in our daily lives? This is a complex problem, with several approaches to it. Here, we were interested in determining the minimum luminance contrast to the background scene required to achieve detection and shape perception. To investigate this, we used natural videos with briefly appearing natural events, varying in timing of appearance, shape, position, and contrast. We found that there is an interplay between the timing of the event, its position, and the contrast needed for detection. However, for correct shape perception, timing was not a relevant variable. A lower contrast was required for event detection than for correct shape perception. We conclude that contrast alone can affect stimulus detection, but other parameters might interact with it in this task.